RESISTANCE PATTERNS OF URINARY ISOLATES IN A TERTIARY INDIAN HOSPITAL - Hasan, Azra S.; Nair, D.; Kaur, J; Baweja, G.; Deb, M; Aggarwal, P. (Journal of Ayub Medical College Abbottabad, 2007)
Background: To analyze the pathogenic organisms recovered from patients with urinary tract infection in a tertiary Indian hospital setting along with determination of the occurrence and antimicrobial sensitivity of uropathogens on a retrospective basis during a period of one year. Methods : A total of 5073 urine samples were processed. Urine culture was done using conventional microbiological techniques. Biochemical testing was used to identify the organisms and antibiotic sensitivity was done by the Kirby Bauer method. Results: A total of 2436 uropathogens were isolated. E coli were seen in 50.7% samples followed by Klebsiella sp (27.6%). Staphylococcus aureus was the commonest Gram- positive isolate (1.5%). Urinary tract infection (UTI) was seen in 70.5% females as compared to 29.5% males. A high recovery of isolates was noted from July to September. Multi drug resistance was commonest with Enterococcus (78.8%) followed by Pseudomonas (65.1%). Drugs, which retained usefulness for Gram-negative isolates, were amikacin, norfloxacin and cefotaxime. For Gram-positive isolates, vancomycin, teicoplanin, lincomycin and Norfloxacin were very effective. Conclusions: Our study highlights the changing etiology of UTI and emergence of drug resistance within the Indian subcontinent. Keywords: Urinary Tract Infections, Pathogens, Antibiotics